Making the Blood Broil: Conflicts Over Imagined Rurality in Peri-Urban Australia. (1st January 2017) - Taylor, Elizabeth; Butt, Andrew; Amati, Marco
Abstract : A key challenge for planning the peri-urban internationally derives from the ability of land-use change to outstrip the development of new concepts and understandings. There are few places where this is more apparent than in the peri-urban areas of Melbourne, Australia, where applications to develop technologically sophisticated broiler or poultry farms are fiercely opposed by local residents and amenity migrants with attendant imaginaries of local community and extensive rural agricultural production. This paper presents the results of an analysis of development application appeals to show how the poultry industry negotiates with the planning system and manages community expectations in a broad swath of Melbourne's exurbia. In particular, we question the relevance of the rural–urban duality for planning this space and argue the need for new concepts to lessen the conflict in these hybridized spaces of third nature.